Exploring Thematic Trends of Online Child Safety: A Bibliometric Study on Social Media and Paedophilia in Indonesia - Saputra, Gemilang Bayu Ragil; Nurliana; Anwar; Yunus, Andi Hikmawati; Muttalib, Sitti Raodha (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study aims to map the development, thematic structure, and research trends of scholarly publications on social media and paedophilia in Indonesia. Using a bibliometric approach, the research quantitatively examines how academic attention to online child sexual exploitation has evolved and identifies dominant themes and emerging directions within the field. Data were collected from Google Scholar using the keywords media, social, paedophilia, and Indonesia, covering journal articles published between 2020 and mid-2025. An initial dataset of 840 articles was retrieved through the Publish or Perish application, followed by a rigorous data cleaning and relevance selection process that resulted in 438 articles for analysis. Bibliometric analysis was conducted using the Bibliometrix package and Biblioshiny interface to generate publication trends, citation patterns, keyword co-occurrence networks, and thematic mappings. The results show a sharp increase in publications from 2020 to 2023, followed by slower growth in 2023–2024 and a decline in 2024–2025. In contrast, citation rates rose significantly in 2024–2025, indicating increasing scholarly impact despite reduced output. Dominant themes center on children, sexual violence, media, and protection, while recent trends highlight a shift toward policy, counseling, and intervention-oriented research. These findings demonstrate an evolving, solution-focused research landscape on online child safety in Indonesia.